Analisis Depresiasi dan Kebijakan Pengelolaan Sumberdaya Ikan Layang di Wilayah Perairan Kota Ambon - Janer Sangaji; Tridoyo Kusumastanto; Sahat M.H. Simanjuntak (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Generally, fishery resources are open access which means that anyone can participate without having these resources. This is shown by an increase in the utilization of fish resources that will lead to a crisis in which when the rate of exploitation goes beyond the ability of regeneration that makes the catches more economical (economic overfishing). Moreover, this will take place in conditions of uncontrolled fishing. The main factor causing this crisis is the uncontrolled human intervention toward the existing fishery resources. The exploitation of these resources can lead to an imbalance between the input and the potential capture of fish resources so that it can lead to over-fishing, overcapacity, inefficiency arrest, resource rents decline, degradation of the resource stock and a decrease in production. The degradation impact of small pelagic fish resource, especially Layang fish in Ambon also is the reduction of producer welfare, especially the welfare of fishermen and coastal communities. This is due to, among others, the lack of control from the government as the authors,, and the lack of understanding of resource actors (local fishermen) about the nature of fish resources which are open access. Thus, the calculation of the depreciation of small pelagic fish resources, especially lyang fish, and welfare aspects which are considered important to know as a point of reference as well as an early warning signal to determine whether the extraction of small pelagic fish resources, especially layang fish in Ambon has exceeded their capabilities.